Solution:
![3 {x}^(2) = - 4 + 8x](https://img.qammunity.org/2023/formulas/mathematics/high-school/x21ne7ihv9hm29kc69baupdbsmpwrla5ao.png)
Let us transpose -4 and 8x to the Left Hand Side. So we are left with 0 on the Right Hand Side.
![= > {3x}^(2) + 4 - 8x = 0](https://img.qammunity.org/2023/formulas/mathematics/high-school/utb1v2sg5ym0g0u352jvgb6xcgclto1aze.png)
Now, arrange the expression in standard form.
![= > {3x}^(2) - 8x + 4 = 0 \\](https://img.qammunity.org/2023/formulas/mathematics/high-school/iopfig6y31opsgbetf2qtk6bi2hd8vn5nl.png)
Now, split the mid term. Here, 3 × 4 = 12. So, we can split -8x into -2x and -6x.
![= > ({3x}^(2) - 6x )- (2x + 4) = 0 \\](https://img.qammunity.org/2023/formulas/mathematics/high-school/a7q1k894i3kw2n75lloitgpljqjuhejax0.png)
Now, take 3x common from the first expression and 2 from the second.
![= > 3x(x - 2) - 2(x - 2) = 0 \\ = > (3x - 2)(x - 2) = 0](https://img.qammunity.org/2023/formulas/mathematics/high-school/3r9hopnkb3ur9qs0lguv5hs8zsd070z184.png)
When, two terms are equal to 0, then each term is equal to zero.
![= > 3x - 2 = 0 \: \: and \: x - 2 = 0 \\ = > 3x = 2 \: \: and \: x = 2 \\ = > x = (2)/(3) \: \: and \: \: 2](https://img.qammunity.org/2023/formulas/mathematics/high-school/wnnkhci1kbxz0kfyntkdl34jmdu1y7l43q.png)
Answer:
![x = (2)/(3) \: \: and \: \: 2](https://img.qammunity.org/2023/formulas/mathematics/high-school/5uye7xdkbnsny8flohzlsbs2x4evtn4vta.png)
Hope you could understand.
If you have any query, feel free to ask.